The Digital Communication Strategies of Regional DMOs at the Time of Covid-19 - De Filippo, Marcella; Bencivenga, Angelo; Colangelo, Delio; Pepe, Angela (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
In a highly competitive arena such as the tourism industry, the creation and management of a distinctive and attractive destination image and a communication strategy are fundamental. Destinations with a strong and positive image have the greatest chance of being chosen by tourists in the purchasing process (Goodrich 1978; Woodside, Lysonsky 1989). Regarding the Destination Management Organization (DMO), several difficulties must be considered for the realization of a communication strategy: the heterogeneity of tourism products, the fragmentation of tourism system, different aims of tourism actors. Tourism destination management aims at integrating the characteristics of a territory analysis, the existing supply, the potential of the tourism system and developing a programmatic strategy and synergistic action of all operators in the sector. For the development of a territory, the coordinated and integrated action of the DMO is essential to implement a effective tourism strategy. The crisis triggered by the current pandemic has represented, in some cases, an opportunity to accelerate the evolutionary process towards the concept of DM&MO (destination management and marketing organization). Compared to the past, DMOs must formulate concrete answers to face the emergency through broader actions and integrated system approaches that include different areas of intervention at governance level (McKercher, 2020). It is therefore necessary for DMOs to reconfigure themselves as a destination developer, facilitating the processes of development and defense of the territory competitiveness (Sainaghi, 2005). The paper analyzes the main actions implemented by regional DMOs to counter the negative effects of the Covid 19 pandemic. The spread of the virus worldwide has had a shock effect on almost all economic sectors and, in particular, on tourism which needs travel and interaction between people, two conditions denied by many national authorities to safeguard the health of citizens. However, this phase of "tourist immobility" can be seen, from DMOs point of view, as an opportunity to rethink tourism strategies, offering training and reflection opportunities to touristic operators, consolidating user loyalty and prepare the relaunch of their supply. The goal of the study is to analyze the actions implemented by the DMOs of the Italian regions during the pandemic period, verifying and classifying the actions and strategies put in place to react to this moment of serious crisis of the tourism sector.